Role of Schooling in Socialisation: A Comparative Study of Madrasas and Government Schools of Old Bhopal - Ansari, Mohd Faisal (JOURNAL OF TEACHER EDUCATION AND RESEARCH, 2012)
Education plays a prominent role in the socialisation of children. The school’s role as a socialising agent is that it provides the intellectual and social experiences from which children develop the skills, knowledge, interests and attitudes that characterise them as an individual and that shape their abilities to perform adult roles. Being a democratic country India gives right to the minorities to open their institution to preserve their culture and number of institutions are providing education to the minority groups. These institutions frame their curriculum and also select the subjects as per their requirement. It is also the matter of concern that their process of socialisation is bit different from the government and other institutions. It is a big and moot question that whether the institutions are having some different types of socialisation process. For seeking the answer, the present research was designed. The present research was quantitative in nature. For achieving the objectives, survey method was adopted. Sample was selected through stratified random sampling. First 10 schools and 10 madarsas were selected from old Bhopla through a lottery method. From each school and madarsa, six teachers were approached and a self-constructed tool was administered. Results revealed that there is a significant difference in the socialisation process between schools and madarsas. Government elementary schools teacher reported that they arranged more activities for socialisation of the students than that of madrasa. On all the six dimension of the socialisation process the schools precede to Madrasas. The boys’ schools were at par with the boys’ madarsas; the difference between the two is not significant. That is why, the null hypothesis was accepted, which speaks that there is no significant different between the two. While seeing dimension-wise data boys school and madrasa were alike except curriculur and co-curricular activities. On the other hand, girls’ madrasa and girl schools were significantly different. The reasons might be variant, the girls’ madarsas mainly cater the first generation learners and the students of the traditional families. In the same way dimension-wise government girls’ schools significantly played a better role in the socialisation process than the madrasas. The results of the study inspires for further investigation of the reasons of that wide difference between the two types of institution.